Effect of Various Pretreatments on Quality Attributes of Vacuum-Fried Shiitake Mushroom Chips. (16th January 2018) - Ren, Aiqing; Pan, Siyi; Li, Weirong; Chen, Guobao; Duan, Xu
Abstract : The objective of this study is to investigate the effects of pretreatments on the quality of vacuum-fried shiitake mushroom slices. Four different pretreatments addressed in this study were (1) blanching as control, (2) blanching and osmotic dehydration with maltodextrin (MD) solution, (3) blanching, osmotic dehydration, and coating with sodium carboxymethyl cellulose (CMC), (4) blanching and osmotic dehydration, followed by freezing. All samples were pretreated and then fried in palm oil at 90°C with vacuum degree of −0.095 MPa for 30 min. The results showed that pretreatments significantly( p < 0.05 ) affected the moisture content, oil content, color, water activity( a w ), total phenolic content, and sensory evaluation of shiitake mushroom chips. The blanching, osmotic dehydration, and coating pretreatment could improve color and sensory evaluation and also minimize the oil uptake of fried chips, whereas this treatment caused the highest reduction of total phenolic contents. There were no significant( p > 0.05 ) differences of fried chip in the texture among the four different pretreatments. Thea w values of all the fried chips were less than 0.38, indicating that the products had a long shelf life. Therefore, the blanching, osmotic dehydration, and coating pretreatment before vacuum frying was the most suitable pretreatment for vacuum-fried shiitake mushroom chips.